TWO-DIMENSIONAL MODEL OF FLUID FLOW AND DISTRIBUTION OF NUTRIENT CONCENTRATION IN A MICROFLUIDIC DEVICE - PAWEŁ WRONISZEWSKI (TASK Quarterly, 2011)
During the past few years, the process of miniaturisation in the field of biochemical laboratory equipment led to the introduction of the so-called “lab-on-a-chip” microdevices, which combine separate functional units into a complex, multifunctional apparatus. Fluid dynamics plays an essential role in the development of such equipment, since frequently the major part of chemical analysis is based on soluble analytes. In this work, we consider a device for the analysis of cell growth under different conditions.